Skeletal Lipocalin-2 Is Associated with Iron-Related Oxidative Stress in ob/ob Mice with Sarcopenia - Eun Bee Choi; Jae Hun Jeong; Hye Min Jang; Yu Jeong Ahn; Kyu Hyeon Kim; Hyeong Seok An; Jong Youl Lee; Eun Ae Jeong; Jaewoong Lee; Hyun Joo Shin; Kyung Eun Kim; Gu Seob Roh (MDPI AG, 2021)
Obesity and insulin resistance accelerate aging-related sarcopenia, which is associated with iron load and oxidative stress. Lipocalin-2 (LCN2) is an iron-binding protein that has been associated with skeletal muscle regeneration, but details regarding its role in obese sarcopenia remain unclear. Here, we report that elevated LCN2 levels in skeletal muscle are linked to muscle atrophy-related inflammation and oxidative stress in leptin-deficient ob/ob mice. RNA sequencing analyses indicated the LCN2 gene expression is enhanced in skeletal muscle of ob/ob mice with sarcopenia. In addition to muscular iron accumulation in ob/ob mice, expressions of iron homeostasis-related divalent metal transporter 1, ferritin, and hepcidin proteins were increased in ob/ob mice compared to lean littermates, whereas expressions of transferrin receptor and ferroportin were reduced. Collectively, these findings demonstrate that LCN2 functions as a potent proinflammatory factor in skeletal muscle in response to obesity-related sarcopenia and is thus a therapeutic candidate target for sarcopenia treatment.